2010
DOI: 10.1002/hbm.21002
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and parietal contributions to arithmetic fact retrieval: A parametric analysis of the problem‐size effect

Abstract: The goal of the present study was to investigate the neuroanatomical basis of arithmetic fact retrieval. The rationale was that areas playing a crucial role in arithmetic fact retrieval should show a systematic increase of activation with increasing retrieval effort. To achieve this goal, we utilized the problem-size effect as this is known to be systematically related to retrieval effort. In contrast to many previous studies, we here took a parametric approach to account for the continuous increase of retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Andres et al (2011) also found no activation in the angular gyrus for multiplication relative to subtraction, letter reading or even fixation. This region has also been found to be susceptible to task difficulty, that is, easy arithmetic problems consistently elicit greater activation than difficult arithmetic problems (e.g., Grabner et al, 2009;Jost et al, 2011;Stanescu-Cosson et al, 2000;Zhou et al, 2007).…”
Section: Geom > Tool Conjunctionmentioning
confidence: 99%
“…Andres et al (2011) also found no activation in the angular gyrus for multiplication relative to subtraction, letter reading or even fixation. This region has also been found to be susceptible to task difficulty, that is, easy arithmetic problems consistently elicit greater activation than difficult arithmetic problems (e.g., Grabner et al, 2009;Jost et al, 2011;Stanescu-Cosson et al, 2000;Zhou et al, 2007).…”
Section: Geom > Tool Conjunctionmentioning
confidence: 99%
“…Although activation in frontal areas of the brain is frequently observed during calculation, these have been shown to be related to general task demands, such as working memory and attention, instead of being specifically related to the neurocognitive processes underlying calculation (Menon, Rivera, White, Glover, & Reiss, 2000). Moreover, it has been shown that brain activation during calculation is modulated by specific factors such as the size of the arithmetic problems (Jost, Khader, Burke, Bien, & Rosler;Stanescu-Cosson et al, 2000) which is often defined as the product of the operands. Other factors that have been revealed to modulate the brain responses measured during calculation are the type of operations, such as the difference between addition and subtraction (Ischebeck et al, 2006;Kong et al, 2005), and the strategies used to solve arithmetic problems (Grabner et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…This view has been completed by further studies suggesting the additional involvement, closely related to the demands imposed by arithmetic fact retrieval, of the medial frontal cortex (e.g. Jost et al, 2011).…”
Section: Introductionmentioning
confidence: 98%